Тhe dominant factors during water treatment in the beverage production - Samchenko, Iryna; Oliynyk, Svitlana (My University, 2019)
Identified dominant factors in water treatment contributes to obtaining treated water for the high stability of the finished product. Виявлені домінуючі фактори очищення води сприяють отриманню очищеної води для високої стійкості готового продукту.
Keywords: водопідготовка; water treatment; напої; beverage; фільтрування; filtration; очищення; purification; кафедра біотехнології продуктів бродіння і виноробства